The Geographical Distribution of Laryngeal Cancer in Iran from 2004 to 2014 - Safavi Naeini, Ali; Raad, Nasim; Eslami, Abdolaziz; Emami, Habib; Moradi, Alireza; Noori, Enayatollah (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2023)
Background: Laryngeal cancer accounts for about 1 to 2 % of all cancers; this incidence rate depends on the geographical region and ethnicity. Due to the lack of a comprehensive epidemiological study on laryngeal cancer in recent years, we designed this study to investigate the incidence and geographical distribution of laryngeal cancer. Aim: This study aimed to investigate the incidence and geographical distribution of laryngeal cancer in Iran from 2004 to 2014. Methods: The data collected from the Iranian National Cancer Data System registry, all the cases of laryngeal cancer (with topography code 32 and histology of laryngeal cancer) have been retrieved and analyzed from a comprehensive cancer database during the 11 years’ period. Then statistical data were analyzed by SPSS, version 16. Results: During the 11-year study, 13,241 new cases of laryngeal cancer were recorded, of which 11454 were men (86%) and 1788 were women (14%). According to this assessment, North Khorasan, Sistan and Baluchestan, and East Azerbaijan provinces had the highest growth rate, and North Khorasan, Gilan, and Kerman provinces with the highest incidence rates of 4.44, 3.29, and 2.23 per 100,000 respectively, between 2004 and 2014. Conclusion: According to the results of this study, the incidence rate of laryngeal cancer, especially in women, is increasing in Iran. Further studies are needed to investigate the causes of increased incidence.